Exploring the Beliefs of Elementary School Teachers Currently Implementing the Continuous Assessment Component of the Secondary Entrance Assessment Programme in Trinidad - Maharajh, Mahindranath (My University, 2015)
Employing a qualitative, single-case, within-site approach, this study explored the epistemological, ontological, and axiological beliefs that have informed the approach used in the development of the Continuous Assessment Component (CAC) of the Secondary Entrance Assessment (SEA) examination, and compared these beliefs to those held by teachers currently enacting the curriculum. It also specifically seeks to provide some insight into the apparent success of CAC implementation along the belief dimensions of change in the classroom of one Standard 4 teacher at a primary school in Trinidad and Tobago. Data were collected through interviews, observations, and document analysis. The findings revealed that while there was significant correlation between the teacher’s beliefs and those contained in the CAC curriculum documents, there were some deficiencies in the balance of values needed for a balanced curriculum.
Keywords: Secondary Entrance Assessment examination; Continuous Assessment Component; Curriculum implementation; Primary school teachers; Teacher attitudes; Case studies; Trinidad and Tobago